2013
DOI: 10.1387/ijdb.130068ja
|View full text |Cite
|
Sign up to set email alerts
|

The spermatogonial stem cell niche in testicular germ cell tumors

Abstract: Spermatogonial stem cells (SSCs) are pluripotent elements found in the adult seminiferous epithelium between Sertoli cells and a basal lamina which covers the multilayered external wall of peritubular myoid cells. The microenvironment of this pluripotent stem cell niche creates the complex and dynamic system that is necessary for the initiation of spermatogenesis, but this system also contains factors which can potentially collaborate in the progression of testicular germ cell tumors (TGCTs). In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…PGCs at genital ridge are called gonocytes and further mature into oogonia and spermatogonia [2,[42][43][44] under strict regulation of the genomic constitution (XX vs XY) and the (gonadal) micro-environment. In an XX constitution the transcription factor SRY will be expressed leading to SOX9 expression and the formation of Sertoli cells: the supporting cells in the testis that guide gonocytes into maturation along the male germ cell lineage [60][61][62][63]. If SRY is not (sufficiently) expressed (physiological in XY condition), granulosa cells will be formed instead which, in the presence of e.g.…”
Section: Normal Germ Cell Developmentmentioning
confidence: 99%
“…PGCs at genital ridge are called gonocytes and further mature into oogonia and spermatogonia [2,[42][43][44] under strict regulation of the genomic constitution (XX vs XY) and the (gonadal) micro-environment. In an XX constitution the transcription factor SRY will be expressed leading to SOX9 expression and the formation of Sertoli cells: the supporting cells in the testis that guide gonocytes into maturation along the male germ cell lineage [60][61][62][63]. If SRY is not (sufficiently) expressed (physiological in XY condition), granulosa cells will be formed instead which, in the presence of e.g.…”
Section: Normal Germ Cell Developmentmentioning
confidence: 99%
“…In vitro propagation of SSCs requires glial cell line-derived neurotrophic factor (GDNF) (Kubota et al, 2004; Ryu et al, 2005), which is secreted from Sertoli cells for maintenance of SSCs in the testis (Meng et al, 2000), as well as other growth factors, such as basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) are required for in vitro propagation of SSCs (Kubota et al, 2004; Rastegar et al, 2013). In general, physical interaction of SSCs with the basal epithelial membrane is required to provide a microniche for self-renewing (Oatley and Brinster, 2012; Phillips et al, 2010; Ryu et al, 2006; Silvan et al, 2013). When primary SSCs are derived from the testis and proliferated in vitro , mouse embryonic fibroblasts (MEFs) are the most commonly used feeder cells that play a role of such microniche by allowing secure attachment and proliferation of SSCs.…”
Section: Introductionmentioning
confidence: 99%
“…A nonsense mutation in plzf gene showed defective spermatogenic self-renewal [29]. Silvan et al [30] reported that MCSF interacts with GDNF and acts specifically on undifferentiated SSCs and that its effect causes spermatogonia self-renewal rather than differentiation.…”
Section: Discussionmentioning
confidence: 99%